Structural Equation Model of the Variables Affecting the Online Shopping Behavior of Generation-Y - Tivarat Sriratree; Opal Suwannamek; Chalita Srinuan (My University, 2024)
Purpose: 1) To investigate the goodness of fit of the SEM of the variables affecting the online shopping behavior of Generation Y in Thailand. 2) To develop the SEM of the variables affecting the online shopping behavior of Generation Y in Thailand. 3) To study the direct, indirect, and total impact of the variables affecting the online shopping behavior of Generation Y in Thailand. Method: The research applied the literature review, and an analysis on the concepts, theories and principles. This mixed research methodology included a quantitative research method, questionnaire, qualitative research method, and in-depth interview to verify the results from the quantitative research. To collect the data, 300 sets of questionnaires were distributed to consumers who had purchased online products. Data were analyzed by content analysis and Structural Equation Model (SEM). Results and Discussions: The research results showed that the hypothesis test results supported the research with statistical significance. The purchase intention had the highest impact on the online shopping behavior, followed by customer innovation and perceived usefulness, respectively. The structural equation model (SEM) of the purchase intention, customer innovation and perceived usefulness had a direct impact on the online shopping behavior of Generation Y, which was consistent with the goodness of fit. Furthermore, consumers wanted to try new things, needed more challenges, and loved using the Internet that was very convenient and saved their time searching for products. They were able to do the transaction on one platform via social media, which facilitated the entrepreneur to build a business opportunity for efficient competitiveness Research Implications: At present, the Internet has a crucial role and influence on people’s daily routines in terms of learning, studying, entertainment, and business. Thus, the use of the Internet will continue to increase; such as, to search for competitor’s information, communicate with customers, and conduct public relations. The use of the Internet also conveniently facilitates communication and access to new target groups. Everyone can purchase or search for a new product easily from anywhere worldwide at a low cost and in a short time, which greatly generates business opportunities. However, the increase of purchasing via social media has resulted in increased usage of Facebook Pay, Instagram Shopping, and LINE OA (Official Account). Originality/Value: Therefore, social media has simplified the buyer's ability to buy products and be able to do transactions on one platform. Nevertheless, the key concern is the more expensive advertisement costs due to the higher number of sellers. For example, Omnichannel is an inclusive buy-and-sell platform that most retailers are interested in because it supports business growth and provides more payment channels to the customer. Once the customer has the perceived usefulness, enjoys using it, and would like to try the new products via the purchase intention, it would affect the online shopping behavior.
Keywords: Consumer Perception and Purchasing Behavior